2011
DOI: 10.3748/wjg.v17.i7.946
|View full text |Cite
|
Sign up to set email alerts
|

Primary clear cell carcinoma in the liver: CT and MRI findings

Abstract: The imaging characteristics of PCCCL are similar to those of CHCC and could be useful for differentiating these from other liver tumors (such as hemangioma and hepatic metastases). PCCCLs are more prone than CHCCs to form pseudo capsules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 25 publications
2
26
3
Order By: Relevance
“…Because of hypervascular blood supply, typical HCC shows early enhancement at HAP, and rapid washout at PVP or HDP [67,68]. The imaging characteristics of PCCCL are similar to those of HCC [69]. These imaging features may help differentiate PCCCL from other liver tumors.…”
Section: Primary Clear Cell Carcinomamentioning
confidence: 75%
“…Because of hypervascular blood supply, typical HCC shows early enhancement at HAP, and rapid washout at PVP or HDP [67,68]. The imaging characteristics of PCCCL are similar to those of HCC [69]. These imaging features may help differentiate PCCCL from other liver tumors.…”
Section: Primary Clear Cell Carcinomamentioning
confidence: 75%
“…Radiographically it can be difficult to distinguish PCCCL from other types of HCC, though there is evidence that PCCCL has a propensity to form pseudo-capsules visible on CT or MRI [10,11]. In our case the mass did not evince such a pseudo-capsule, though most importantly the imaging did not find evidence of malignancy in other organ systems, which helped to establish that the liver was the origin of the cancer.…”
Section: Clinical and Experimental Pathologymentioning
confidence: 59%
“…There are several studies which show a sensitivity of 92% [20] for double contrast enhanced MRI compared with 50% sensitivity in case of single contrast-enhanced MRI [21] in diagnosing nodules between 1-2 cm. In 2003, it has been demonstrated that angio-MRI increase the diagnostic accuracy of lesions less then 1 cm when comparing with CT (76% versus 61%), and particularly in case of lesions between 1 and 2 cm diameter (84% versus 47%) [22].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, MRI correctly diagnosed the HCCs misdiagnosed by CEUS and a sensitivity of 91.4%, with a specificity of 98.9% in HCC diagnosis has been found, regardless of nodules size. The various aspects of tumors in MRI depend on tumor architecture, grading, stromal component, as well as intracellular content [20]. The sensitivity of MRI in the detection of HCC is lower in cases with cirrhosis, in advanced stages and in the presence of ascites [23].…”
Section: Discussionmentioning
confidence: 99%